Knowledge, eating patterns, and hypertension among elderly in the coastal areas of Bangkalan, Indonesia - Festi Wiliyanarti, Pipit; Wulandari, Fitri; Sumarliyah, Eni (International Journal of Public Health Science (IJPHS), 2024)
Hypertension is a non-communicable disease which frequently occurs in the elderly. This study aimed to assess hypertension and knowledge as well as hypertension and eating patterns among elderly in the coastal areas. The design of this study is cross-sectional study. The population in this study were elderly with hypertension who lived in the Sukolilo Health Center area in Bangkalan. The sample was selected using simple random sampling of 110 elderlies. The inclusion criteria were elderly who were aged ≥60 years old with systolic blood pressure (SBP) of >140 mmHg and diastolic blood pressure (DBP) of >90 mmHg. The instrument was food frequency questionnaire (FFQ). The blood pressure was measured by using standard operating procedures. The data were analyzed by the Spearman’s rank test. The results indicated that most of the respondents were lack of knowledge of 66 people (29.1%) and had a poor eating pattern of 78 people (70.9%). Most of the respondents were in the moderate hypertension of 52 people (47.3%). The statistical analysis indicated a relationship between knowledge and the incidence of hypertension of p=0.004 (p<0.05; r=0.974). In conclusion, understanding about blood pressure control is required to prevent hypertension.